GAMBARAN PENGELOLAAN KELAS OLEH GURU PAUD SE-KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Puspitasari, Enda Puspitasari; ', Sutanti; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: the aimed of this study to determine the class management by early childhood teachers throughout Payung Sekaki District of Pekanbaru. Population and sample in this research amount to 21 people S1 early childhood teachers in Sub District of Payung Sekaki Pekanbaru. The data collection techniques that use a questionnaire. Data analysis technique using a percentage formula. The results were obtained by early childhood teachers classroom management throughout Payung Sekaki District of Pekanbaru overall gain a percentage of 89.74% which is in the category "Very Often". Based on the analysis of teachers' working lives, showing the work of teachers affect the ability of classroom management by early childhood teachers throughout Payung Sekaki District of Pekanbaru. It can be seen from the data analysis, the chi-square calculation results obtained figure of 41.868%. This figure compared with the chi-square value in the table with df of 26 is at 5% significance level that is equal to 38.885%, showing the results of calculation of chi square is greater than the chi square results in the table (41.866%> 38.855%). Based on the analysis of the training, show training does not affect the ability of classroom management by early childhood teachers throughout Payung Sekaki District of Pekanbaru. It can be seen from the results of the chi square analysis calculation results obtained figure of 8,399%. This figure compared with the chi-square value in the table with df equal to 4 to 5% significance level that is equal to 9.488%, showing the results of calculation of chi square is smaller than the results of the chi square on the table (8.399% <9.488%). Keywords: Management Class